Prenatal Diagnosis of Recurrent Distal 1q21.1 Duplication in Three Fetuses With Ultrasound Anomalies - Ji, Xiuqing; Pan, Qiong; Wang, Yan; Wu, Yun; Zhou, Jing; Liu, An; Qiao, Fengchang; Ma, Dingyuan; Hu, Ping; Xu, Zhengfeng (Frontiers in Genetics, 2018)
Bankground The phenotype of duplication of 1q21.1 region is variable, ranging from macrocephaly, autism spectrum disorder, congenital anomalies, to a normal phenotype. Few cases have been reported in the literature regarding prenatal diagnosis of 1q21.1 duplication syndrome. The current study presents prenatal diagnosis of 1q21.1 duplication syndrome in three fetuses with ultrasound anomalies. Case presentation Three fetuses from three unrelated families were included in the study. The prenatal ultrasound examination showed nasal bone loss in Fetus 1 and Fetus 3, as well as duodenal atresia in Fetus 2. Chromosomal microarray analysis was performed to provide genetic analysis of amniotic fluid and parental blood samples. The CMA results revealed two de novo duplications of 1.34 Mb and 2.69 Mb at distal 1q21.1 region in two fetuses with absent nasal bone, as well as a maternal inherited 1.35-Mb duplication at distal 1q21.1 in one fetus with duodenal atresia. Conclusions The phenotype of 1q21.1 duplication syndrome in prenatal diagnosis is variable. The fetuses with nasal bone loss or duodenal atresia may be related to 1q21.1 duplication and chromosomal microarray analysis should be performed.